2013
DOI: 10.1136/bmjopen-2013-003121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical trial findings on Bell's palsy management in general practice in the UK 2001–2012: interrupted time series regression analysis

Abstract: ObjectivesTo measure the incidence of Bell's palsy and determine the impact of clinical trial findings on Bell's palsy management in the UK.DesignInterrupted time series regression analysis and incidence measures.SettingGeneral practices in the UK contributing to the Clinical Practice Research Datalink (CPRD).ParticipantsPatients ≥16 years with a diagnosis of Bell's palsy between 2001 and 2012.Interventions(1) Publication of the 2004 Cochrane reviews of clinical trials on corticosteroids and antivirals for Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 38 publications
2
51
0
4
Order By: Relevance
“…For example, interventions recommended as core treatment (particularly exercise, weight loss and the provision of written information) for knee pain among older adults were underused 3. Despite clinical trial findings showing a clear impact on primary care management of Bell's Palsy, a significant proportion of patients did not receive effective treatment (ie, corticosteroids) 4. Conversely, many interventions that have been proven to be ineffective continue to be used, for example, antibiotics for acute respiratory tract infection 5.…”
Section: Introductionmentioning
confidence: 99%
“…For example, interventions recommended as core treatment (particularly exercise, weight loss and the provision of written information) for knee pain among older adults were underused 3. Despite clinical trial findings showing a clear impact on primary care management of Bell's Palsy, a significant proportion of patients did not receive effective treatment (ie, corticosteroids) 4. Conversely, many interventions that have been proven to be ineffective continue to be used, for example, antibiotics for acute respiratory tract infection 5.…”
Section: Introductionmentioning
confidence: 99%
“…A recent UK-wide study of management and referral practices revealed that, in 2012, 44% of all Bell's palsy diagnoses were untreated, while only 6.6% were referred to secondary care, usually otolaryngology, ophthalmology, or neurology. 12 Fewer patients were actually referred in 2012 than in 2001. Clearly, large numbers of patients are not being treated effectively in the acute setting and most patients with incomplete symptom resolution are not referred on to secondary services.…”
Section: Current Bell's Palsy Management: Good Bad and Indifferentmentioning
confidence: 98%
“…Studien viste at det var en økning i forskrivelse av prednisolon til pasienter med Bells parese etter 2007, men at 44 % av pasientene fortsatt ikke fikk noen form for behandling i 2012 (1). Noen av disse pasientene hadde trolig andre sykdommer som gjorde at prednisolon ikke ble gitt.…”
Section: Korrekt Behandling?unclassified
“…30 -40 per 100 000 innbyggere (1), noe som tilsvarer 1 500 -2 000 pasienter per år i Norge. Sykdommen forekommer i alle aldersgrupper, men insidensen øker med alderen (1). Omtrent 70 % av pasientene får normal nervefunksjon i løpet av seks måneder uten noen form for behandling, mens de resterende 30 % får sekvele med permanent svakhet av ansiktsmuskulaturen, muskelkontraktur og/eller synkinesier (2).…”
unclassified